2014
DOI: 10.1002/biot.201300448
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant defense parameters as predictive biomarkers for fermentative capacity of active dried wine yeast

Abstract: The production of active dried yeast (ADY) is a common practice in industry for the maintenance of yeast starters and as a means of long term storage. The process, however, causes multiple cell injuries, with oxidative damage being one of the most important stresses. Consequentially, dehydration tolerance is a highly appreciated property in yeast for ADY production. In this study we analyzed the cellular redox environment in three Saccharomyces cerevisiae wine strains, which show markedly different fermentativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…In our opinion, these results suggest that, in addition to the stability of the plasma membrane, other factors may play an important role in determining the resistance of yeast cells under conditions of dehydration–rehydration. Examples of these other factors are the cell wall structure and cell wall protein content, as demonstrated for the yeast S. cerevisiae (Borovikova, Teparic, Mrsa, & Rapoport, ), in addition to various intracellular protective compounds and reactions (Gamero‐Sandemetrio, Gómez‐Pastor, & Matallana, ; Rapoport, ; Rapoport et al, ; Takagi, ). At the same time, the results of our current study revealed another interesting finding that there do not appear to be any serious changes in molecular organisation and structure of the plasma membrane, which may be important for the maintenance of cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…In our opinion, these results suggest that, in addition to the stability of the plasma membrane, other factors may play an important role in determining the resistance of yeast cells under conditions of dehydration–rehydration. Examples of these other factors are the cell wall structure and cell wall protein content, as demonstrated for the yeast S. cerevisiae (Borovikova, Teparic, Mrsa, & Rapoport, ), in addition to various intracellular protective compounds and reactions (Gamero‐Sandemetrio, Gómez‐Pastor, & Matallana, ; Rapoport, ; Rapoport et al, ; Takagi, ). At the same time, the results of our current study revealed another interesting finding that there do not appear to be any serious changes in molecular organisation and structure of the plasma membrane, which may be important for the maintenance of cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…Induction of genes that perform an antioxidant function, such as that of the thioredoxin reductase TRR1 gene, is observed. High levels of protective disaccharide trehalose, and strong catalase and glutathione reductase activities, have been related with good drying performance in wine (Gamero-Sandemetrio et al 2014). The overexpression of hydrophilin SIP18 in industrial strains decreases ROS after oxidative stress and increases viability after desiccation (Lopez-Martinez et al 2013).…”
Section: Ady Productionmentioning
confidence: 99%
“…This observation reinforces the functional role of this gene with respect to dehydration‐related damage and the correlation between ability to withstand water loss and maintenance of redox homeostasis, as already reported (França et al ., ; Garre et al ., ; Matallana and Aranda, ). Moreover, catalase activity has been identified as one of the biochemical parameters that can be used to predict physiologically relevant phenotypes for wine yeasts of potential interest for ADY production, demonstrating that low level of oxidative defence characterizes the worst performing strains (Gamero‐Sandemetrio et al ., ). Since this gene was upregulated also in CD‐6Sc strain from exponentially growing cells, this work suggests the potential effectiveness of CTT1 as a marker gene for desiccation tolerance in indigenous wine yeasts independently of the growth phase, although its applicability requires further investigation on a large number of strains.…”
Section: Discussionmentioning
confidence: 97%